MOTIVASI PERAWAT TERHADAP PENERAPAN ASUHAN KEPERAWATAN DI RUMAH SAKIT UMUM ALOEI SABOE GORONTALO - Aisah R. Pomatahu (Jurnal Inovasi, 2010)
Nursing is a professional service from as an integral part of health serve based on nursing triek and science have to shape of bio physic, sosial, spiritual serve comprehensively to ward, to individual, family and community, include all the human life proses. Nurse is someone gives the nursing vear direetly and totally to patient, beside the hospital asset to develoved. Nursing has various of health serve it was professional yet in professional nursing practice. The research method that is used the descrutives and using disportinate random sampling with sixty (60) respondents of nurse. The result reaserch data was collected by the questionnaire analyzed statistically with goodman kruskel correlation from education (X), work relation, facilitys, aspects, and the roles off manager to nursing vear in Gorontalo Aloei Saboe Hospital. The result of this researchand data analyzys shows there are motivation relation of the nurses from education, work relation, facalitys aspeets and the roles of manager the nursing vear in Gorontalo Aloei saboe hospital Gn = 0.184. The result of research and disscusion supported by all theory source as well as empiris studies as the result of research before. Clearly that giving the nursing rear in Gorontalo Aloei Saboe Hospital, it could not take from education as a mode to increasing ability, skill or science, beside neaded work harmonious relation to among other, between the higher and the subordinate suppurted by good facilities with the roles of manager to effeetive the management personalia function it always direeted to develoving of nursing.